Gender Differences in Language Learning Strategies - Sumarni Sumarni; Noor Rachmawaty (Ethical Lingua: Journal of Language Teaching and Literature, 2019)
This study investigates the application of language learning strategies by different gender of university students. To do so, memory, cognitive, compensation, metacognitive, affective, and social language learning strategies were investigated. To collect data, the Strategy Inventory for Language Learning (SILL; Oxford, 1990) was administered to male and female student. They, then, were analyzed using descriptive statistics. The findings of the study indicated that students used a wider range of learning strategies and different from those often preferred by their gender. Both female and male often use social strategies while the lowest frequency strategy use both them were different. The results of this study can be useful for language teachers instead of raising their awareness on reducing the gap between the students' language learning strategies and their teaching technique preferences.